Constitutional Law Analysis in the Handling of Idle Land in GR No 48 of 2025 Concerning the Regulation of Areas and Idle Land - Victor Tongam Museka Siregar; Diki Zukriadi (Jurnal Multidisiplin Sahombu, 2026)
This research analyzes constitutional law in the handling of idle land based on Government Regulation Number 48 of 2025 concerning the Regulation of Areas and Idle Land. Focusing on constitutional and juridical aspects, this study evaluates the extent to which the GR aligns with the principles of Indonesia's constitutional law, such as the supremacy of law, social justice, and state resource management for the prosperity of the people as mandated in the 1945 Constitution. Idle land is a significant issue related to land ownership inequality and neglect of the social function of land, requiring state intervention for fair redistribution. The research method uses a normative juridical approach, analyzing legislation such as the Basic Agrarian Law (UUPA) and Government Regulation Number 11 of 2010, as well as court rulings and customary law, to provide a comprehensive review of the legal framework for handling idle land. The research results highlight the complexity of the problem, with factors such as unclear ownership, neglect, and regulatory deficiencies as major challenges. Government Regulation Number 48 of 2025 strengthens regulatory mechanisms by expanding coverage to areas and integrating data-based monitoring. However, obstacles such as lack of inter-agency coordination, technical limitations, and authority conflicts persist. From a constitutional law perspective, this GR supports the rule of law through attribution, delegation, and mandate of authority, ensuring transparent resource management. In conclusion, firm legal steps are necessary, including policy revisions, regulatory strengthening, and inter-agency cooperation. Recommendations include integrating digital technology and community participation for the effectiveness of Government Regulation Number 48 of 2025, to achieve agrarian justice. Further research is needed for more comprehensive solutions.